2016
DOI: 10.1177/1081286514544780
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic analysis of Lennard-Jones systems beyond the nearest-neighbour setting: A one-dimensional prototypical case

Abstract: We consider a one-dimensional system of Lennard-Jones nearest-and next-to-nearest-neighbour interactions. It is known that if a monotone parameterization is assumed then the limit of such a system can be interpreted as a Griffith fracture energy with an increasing condition on the jumps. In view of possible applications to a higher-dimensional setting, where an analogous parameterization does not always seem reasonable, we remove the monotonicity assumption and describe the limit as a Griffith fracture energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 18 publications
1
25
0
Order By: Relevance
“…In the last two decades progress was made in order to derive such macroscopic models from underlying microscopic (discrete) models, see e.g. [7,8,10,11,12,14,15,25,26,27]. This research started with the early contribution by Truskinovsky [29], who emphasizes that macroscopic models for fracture mechanics should contain information on the microscopic length scale of the system.…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades progress was made in order to derive such macroscopic models from underlying microscopic (discrete) models, see e.g. [7,8,10,11,12,14,15,25,26,27]. This research started with the early contribution by Truskinovsky [29], who emphasizes that macroscopic models for fracture mechanics should contain information on the microscopic length scale of the system.…”
Section: Introductionmentioning
confidence: 99%
“…It has been partially addressed by Theil [23], and should be included in further investigations on the subject. The one-dimensional analysis by Braides and Solci [11] suggests that considering longer range of interactions (e.g., next-to-nearest neighbours) could be used in the place of the determinant constraint in order to eliminate non-local effects for non-opening cracks, at the expense of introducing internal and external boundary layers.…”
Section: Discussionmentioning
confidence: 99%
“…Another application field concerns the research trend on generalized continua and their applications such as, for example, reported in for gradient models; in for second gradient models; in for multi‐constituent materials, in for some hints on non‐local problems, in for pantographic structure and in for an asymptotic approach.…”
Section: Discussionmentioning
confidence: 99%
“…7 Meshes m1, m2, and m3 used in the analysis of the corner wall test and the relative displacement fields at the end of the loading phases. in [28] for some hints on non-local problems, in [2,3,34,35,38,52] for pantographic structure and in [18] for an asymptotic approach. Also the analysis of higher-order continua could make good use by effective procedures, see for example the review paper [33] which considers the dynamic case, [17] for graded materials and [4] for micropolar continua.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation